TRACING THE TRAJECTORY OF SOCIAL WELL-BEING PUBLICATIONS: A BIBLIOMETRIC APPROACH (Social Security Management Journal, 2025)
Social well-being is an approach that deals with the quality of social relationships within the wider community. This approach involves a person's social interactions with others while building healthy relationships and providing positive stimulation from social networks. Meanwhile, this studies aims to explore social well-being research-related publishing patterns and trends the most commonly used author keywords in the Scopus and Web of Science (WoS) databases. The eminent software, ScientoPy and VOSviewer, are used to run and execute relevant publication data retrieved from Scopus and WoS. The results showed a positive trend in the growth of social well-being literature in both databases since 1968. The top three research areas that dominate this topic are “psychology”, “public, environmental & occupational health”, and “business & economics”. Based on a country analysis, United States has become an active publisher, followed by the United Kingdom and Australia. Importantly, this studies emphasised the scholarly practices prevalent in social well-being research have impressively propagated. The trends will assist researchers in recognizing various fields in identifying the core areas, proactive institutions, and productive authors published in this knowledge for supplementary investigation. Besides, by examining the most popular keywords, the results of this studies enable researchers to discover the possibility for future research that may be conducted, particularly concerning the annual growth rates, which have been trending in the last five years.